(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
In this text we propose that the novel Mezquina memoria, of the writer Antonio Gil, updates the complex relationship between poetry and history that establishes the La Araucana, of Alonso de Ercilla, as a foundational epic. In our proposal for reading, Mezquina memoria is configured from a hypothesis that constantly frustrates and that said relationship with the impossibility of constructing a story ––unitary, a “meta recit”–– about the writing of Ercilla as an act of poetic creation. In this way, the mythistorical dimension of the novel, gives rise to a critical reading of Chile as a symbolic territory.